CFD Assessment for Small UAV Propeller Aerodynamics - Arafat, Mohammad; Ishak, Izuan Amin; Mohd Marua, Nurshafinaz; Muhammad Razif, Muhammad Rusydi; Mohd Sakri, Fadhilah; Anugraha, Rino Andias (semarak ilmu, 2025)
This study investigates UAV propeller aerodynamics, focusing on key parameters such as mesh resolutions, timestep sizes, rotational speeds and RANS turbulence models. Through comprehensive CFD simulations, the aerodynamic performance of the propeller is assessed across operating conditions from 3,000 to 8,000 RPM. We analyse mesh resolutions ranging from coarse to fine, finding that finer meshes yield more accurate thrust and torque predictions but increase computational costs. Timestep sizes of 0.5°, 1°, 5° and 10° are evaluated, with smaller timesteps offering finer temporal resolution at the expense of additional resources. The thrust and torque coefficients reveal a clear relationship between RPM and aerodynamic performance. Our findings suggest that medium mesh resolution discovers a balance between computational efficiency and accuracy. Differences between experimental and simulation data, especially at higher RPMs, are linked to geometric simplifications in the simulation. This research offers valuable insights for selecting appropriate mesh and timestep sizes, which are crucial for ensuring computational accuracy and resource efficiency.